2022
DOI: 10.21203/rs.3.rs-1204399/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral SARS-CoV-2 Inoculation Causes Nasal Viral Infection Leading to Olfactory Bulb Infection: an Experimental Study

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections can cause long-lasting anosmia, but the impact of SARS-CoV-2 infection, which can spread to the nasal cavity via the oral route, on the olfactory receptor neuron (ORN) lineage and olfactory bulb (OB) remains undetermined. Using Syrian hamsters, we explored whether oral SARS-CoV-2 inoculation can lead to nasal viral infection, examined how SARS-CoV-2 affects the ORN lineage by site, and investigated whether SARS-CoV-2 infection can spread t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 31 publications
1
7
1
Order By: Relevance
“…The data presented herein do not support hematogenous diffusion of SARS-CoV-2 towards the brain, and supports hypothesis of the olfactory retrograde pathway as a preferential portal of entry (Ueha et al, 2022). Brain infection via the olfactory pathway therefore seems a common feature of coronaviruses (Dubé et al, 2018;Shi et al, 2022), regardless of clinical disease presentations.…”
Section: Discussioncontrasting
confidence: 77%
“…The data presented herein do not support hematogenous diffusion of SARS-CoV-2 towards the brain, and supports hypothesis of the olfactory retrograde pathway as a preferential portal of entry (Ueha et al, 2022). Brain infection via the olfactory pathway therefore seems a common feature of coronaviruses (Dubé et al, 2018;Shi et al, 2022), regardless of clinical disease presentations.…”
Section: Discussioncontrasting
confidence: 77%
“…However, the impact of SARS-CoV-2 on each ORN lineage cell has not been sufficiently verified. We previously reported that all ORN lineage cells are impaired by SARS-CoV-2 (19), and in this study, we verified related longitudinal effects for the first time to our knowledge. In the NS area, SARS-CoV-2 infection caused shedding of almost all cells of the OE and greatly thinned the OE.…”
Section: Discussionsupporting
confidence: 86%
“…SARS-CoV-2 infected animal models were prepared following previously reported methods (19,24). In short, the SARS-CoV-2 strain (JPN/TY/WK-521, provided by the National Institute of Infectious Diseases, Japan) was used.…”
Section: Animal Model Preparationmentioning
confidence: 99%
See 2 more Smart Citations